Explicit Evidence on an Implicit Contract - Andrew T. Young; Daniel Levy (Bar-Ilan University, Department of Economics, 2010)
We offer the first direct evidence of an implicit contract in a goods market. The evidence we offer comes from the market for Coca-Cola. We demonstrate that the Coca-Cola Company left a substantial amount of written evidence of its implicit contract with its consumers-a very explicit form of an implicit contract. The contract represented the promise of a five cent (nominal) price and adherence to the 'Secret Formula'. In general, the implicit nature of such contracts makes observation difficult. To overcome this difficulty, we adopt a narrative approach. Based on the analysis of a large number of historical documents obtained from the Coca-Cola Archives and other sources, we offer evidence of the Coca-Cola Company both acknowledging and acting on this implicit contract. We also make another unique contribution by exploring quality as a margin of adjustment available to Coca-Cola. The implicit contract included a promise not only of a constant nominal price but also a constant quality (i.e., 6.5 oz. of the Secret Formula). During a period of over 70 years, we find evidence of only a single case of true quality change. By studying the margin of adjustment the Coca-Cola Company chose in response to changes in market conditions, we demonstrate that the perceived costs of breaking the implicit contract were large. We argue that one piece of direct evidence on the magnitude of these costs is the aftermath 'New Coke's' introduction in 1985.
Keywords: E12; E31; L14; L16; L66; M30; N80; A14; 330; Implicit Contract; Explicit Contract; Invisible Handshake; Customer Market; Long- Term Relationship; Price Rigidity; Nickel Coke; Coca-Cola; Vertragstheorie; Getränkeindustrie; Beziehungsmarketing; Produktqualität